MODELING THE DEVELOPMENT PROCESS OF INCLUSIVE EDUCATION IN UKRAINE - Kovtoniuk, Mariana M.; Kosovets, Olena P.; Soia, Olena M.; Pinaieva, Olga Yu.; Ovcharuk, Vira G.; Mukhsina, Kuralay (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The article presents the results of research on the implementation of the principles of inclusive education in Ukraine, substantiates its relevance in the development of a democratic society and European integration policy. The principles of the state policy in the field of inclusive education, its normative-legal support and international practice of providing educational services to citizens with special needs are described. Advanced experience of inclusion introduction in the educational process of preschool, general secondary, vocational and higher education institutions is analyzed. Official statistics on the total number of people with disabilities in Ukraine; availability of special secondary education institutions (boarding schools) and their contingent; the number of children with disabilities in preschool education institutions, students with disabilities in full-time secondary education institutions, persons with disabilities in vocational education institutions, persons with disabilities among students of higher education institutions etc., have been handled. The importance and expediency of the scientific development of the principles of inclusive education, its practical implementation and study of socio-economic effect are substantiated. Graphic visualization of the correlation between the employed persons with disabilities and persons without disabilities, number of children, pupils, students with special educational needs in education establishments of Ukraine is presented.